Building Capacity : Experiences from Post-Disaster Aceh and Nias - MDF-JRF Secretariat (World Bank, Jakarta, 2014)
The Multi Donor Fund for Aceh and Nias (MDF) and the Java Reconstruction Fund (JRF) have played significant roles in the remarkable recovery of Aceh, Nias and Java, following some of the worst disasters in Indonesia in recent years. The MDF and the JRF, which is patterned after it, are each considered a highly successful model for post-disaster reconstruction. This paper discusses the value of a phased approach to post-disaster reconstruction as a successful means to manage short-term expectations while delivering long-lasting, results of high quality. The natural disasters of late 2004 and early 2005 left a trail of human loss and destruction in Aceh and Nias. In such a scenario, capacity building efforts related to individual and community level investments yielded large returns. Aceh and Nias have emerged from the reconstruction experience in a better position to address these challenges as a result of the capacity building achieved through the recovery process.